Clinical Manufacturing of Regulatory T Cell Products For Adoptive Cell Therapy and Strategies to Improve Therapeutic Efficacy. (31st December 2023) - Baron, Kassandra J.; Turnquist, Hēth R.
ABSTRACT: Based on successes in preclinical animal transplant models, adoptive cell therapy (ACT) with regulatory T cells (Tregs) is a promising modality to induce allograft tolerance or reduce the use of immunosuppressive drugs to prevent rejection. Extensive work has been done in optimizing the best approach to manufacture Treg cell products for testing in transplant recipients. Collectively, clinical evaluations have demonstrated that large numbers of Tregs can be expanded ex vivo and infused safely. However, these trials have failed to induce robust drug-free tolerance and/or significantly reduce the level of immunosuppression needed to prevent solid organ transplant (SOTx) rejection. Improving Treg therapy effectiveness may require increasing Treg persistence or orchestrating Treg migration to secondary lymphatic tissues or places of inflammation. In this review, we describe current clinical Treg manufacturing methods used for clinical trials. We also highlight current strategies being implemented to improve delivered Treg ACT persistence and migration in preclinical studies.